(Electro)chemical expansion during cycling: monitoring the pressure changes in operating solid-state lithium batteries. Issue 20 (10th May 2017) - Zhang, Wenbo; Schröder, Daniel; Arlt, Tobias; Manke, Ingo; Koerver, Raimund; Pinedo, Ricardo; Weber, Dominik A.; Sann, Joachim; Zeier, Wolfgang G.; Janek, Jürgen
Abstract : Monitoring pressure changes in an operating solid-state battery demonstrates the importance of external pressure in ensuring long-term electrochemical performance. Abstract : Solid-state lithium-ion batteries (SSBs) are a promising concept for future energy storage applications. Interestingly, the mechanical effects during operation of SSBs, and their correlation to the electrochemical performance, have rarely been investigated. In such systems, the rigid mechanical coupling between the active phases and the solid electrolyte will lead to more complex non-local strain effects than in the common liquid electrolyte-based lithium-ion batteries, where the chemical expansion or compression of the active phases is accommodated by the liquid electrolyte, and only local mechanical strain within the electrode particles exists. In this work we report on the pressure and height changes within typical solid-state batteries, which were measured in situ during galvanostatic cycling conditions. The continuous volume changes of both the anode and the cathode during lithiation/delithiation are responsible for a highly reproducible cycle of pressure changes during the operation of the solid-state battery cell. Bending and cracking of the solid-state battery cells are observed with X-ray tomography and provide evidence for the critical role of the macroscopic strain generated during cycling. Furthermore, these pressure and dilatometry measurements as well as X-ray tomography underline the importance of external confinement and pressure control for SSBs.